Conversion of coordinate system (circular area) / Rafizah Kechil and Nor Hanim Abd Rahman - Kechil, Rafizah; Abd Rahman, Nor Hanim (Unit Penerbitan JSKM, 2020)
The Cartesian coordinate system provides a straightforward way to describe the location of points in space. Some surfaces, however, can be difficult to model with equations based on the Cartesian system for example, cases in two-dimensional Polar Coordinates often offers as a useful alternative system for describing the location of a point in the plane, particularly in cases involving circles. Alternatively, for three-dimensional cases, extensions of polar coordinates are used, namely by the Cylindrical Coordinates and Spherical Coordinates.